DESCENTRALIZATION AND SOCIAL PARTICIPATION: FINDINGS AND COMPARATIVE ANALYSIS ON BRAZILIAN EXPERIENCIES OF POLITICAL AND ADMINISTRATIVE DESCENTRALIZATION - Edson Luiz Cogo; Valdir Roque Dallabrida (Redes, 2015)
The descentralization of public management in Brazil oportunized by the different experiencies on political-administrative descentralization, is a nowadays issue with a deep relevance for the advancement of democracy, taking in to account the indicators of social participation under the 1988 Brazilian Federal Constitution. The experiences of descentralization in the fields of political and administrative are compared between the Rio Grande do Sul and Santa Catarina States. Also the possibility of social participation in the public management is assessed, under the legal framework in force. Considering the mentioned analysis it is possible to say that although some former error could occur, in both experiences, the Juridical Framework of the Development Regional Councils (RS) allows a major social participation. On the other hand the Regional Development Council (SC) despite being provided for the equally participation between the public sector and the civil society in the formation of their boards, the nomination and appointment of the members is a responsability of the State and the Cityhalls, with what is commited the representative participation of the society in the process.